One plus one: Two free flaps from same donor thigh for simultaneous coverage of two different defects - Susmitha Bandi; Rayidi Venkata Koteswara Rao; Damalacheruvu Mukunda Reddy (Indian Journal of Plastic Surgery)
Introduction: Primary microvascular reconstruction of multiple defects is challenging particularly if it has to be simultaneous. In trauma cases, harvesting two independent free flaps from different sites is very time-consuming and adds to morbidity. To eliminate these disadvantages, we sought to find out a reliable alternative method of harvesting two independent free flaps based on the descending branch of circumflex femoral artery, i.e., one anterolateral thigh (ALT) flap and one rectus femoris muscle flap. Aim: To study the feasibility of transferring two free flaps, i.e., ALT and rectus femoris muscle flap simultaneously from the same thigh for coverage of two different limb defects. Materials and Methods: From 2003 to 2012, five patients with two defects each were managed with a total of ten flaps harvested from five donor sites based on independent pedicles of descending branch of lateral circumflex femoral artery and used to cover severe injuries of extremities. Three cases had both lower limb defects and two cases had one upper limb and one lower limb defect. In each case, one ALT flap and one rectus femoris muscle flap were used for coverage. Results: All reconstructive procedures were completed without any major complications. All flaps survived well. There were no re-explorations and no complications related to donor sites. Conclusion: We conclude that our approach of simultaneous harvest of ALT and rectus femoris muscle from the same thigh offers two flaps for two different defects in terms of economy of donor site and operating time.